2023
DOI: 10.3390/plants12020274
|View full text |Cite
|
Sign up to set email alerts
|

Use of Yucca (Yucca schidigera) Extracts as Biostimulants to Promote Germination and Early Vigor and as Natural Fungicides

Abstract: Climate change is increasing drought and salinity in many cultivated areas, therefore threatening food production. There is a great demand for novel agricultural inputs able to maintain yield under the conditions imposed by the anthropogenic global warming. Biostimulants have been proposed as a useful tool to achieve this objective. We have investigated the biostimulant effect of different yucca (Yucca schidigera) extracts on plant growth at different stages of development under different abiotic stress condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…humate during stress, and its effect at the molecular level. We have previously shown that the model plant Arabidopsis thaliana is a good system to evaluate the effect of biostimulants and to investigate the molecular responses elicited by the biostimulant [35][36][37]. The objective of the present study is to gain insights into the molecular mechanism explaining the effect of potassium humate in plants.…”
Section: Effect Of Potassium Humate (Kh60) On the Growth Of Arabidops...mentioning
confidence: 98%
See 1 more Smart Citation
“…humate during stress, and its effect at the molecular level. We have previously shown that the model plant Arabidopsis thaliana is a good system to evaluate the effect of biostimulants and to investigate the molecular responses elicited by the biostimulant [35][36][37]. The objective of the present study is to gain insights into the molecular mechanism explaining the effect of potassium humate in plants.…”
Section: Effect Of Potassium Humate (Kh60) On the Growth Of Arabidops...mentioning
confidence: 98%
“…However, despite the available information on the effect of humic substances on the interaction with osmoprotective solutes and the plant metabolome, there are few studies on the specific effect of potassium humate during stress, and its effect at the molecular level. We have previously shown that the model plant Arabidopsis thaliana is a good system to evaluate the effect of biostimulants and to investigate the molecular responses elicited by the biostimulant [35][36][37]. The objective of the present study is to gain insights into the molecular mechanism explaining the effect of potassium humate in plants.…”
Section: Introductionmentioning
confidence: 98%